Investigation of the Bragg peak degradation caused by homogeneous and heterogeneous lung tissue substitutes: proton beam experiments and comparison to current clinical dose calculation. (11th December 2020) - Hranek, A; Resch, A F; Georg, D; Knäusl, B
Abstract: Submillimetre structures of lung tissue are not represented in computed tomography images used for radiotherapeutic dose calculation. In order to study the effect experimentally, lung substitutes with properties similar to lung tissue were chosen, namely two types of commercial lung tissue equivalent plates (LTEPs) (CIRS, USA), two types of cork, balsawood, floral foam and konjac sponge. Laterally integrated dose profiles were measured as a function of depth for proton pencil beams (PBs) with an initial nominal energy of 97.4 and 148.2 MeV, respectively. The obtained dose profiles were investigated for their shifting and degradation of the Bragg peak (BP) caused by the materials, expressed as water equivalent thickness (WET) and full width half maximum. The set-up was simulated in the treatment planning system (TPS) RayStation using the Monte Carlo (MC) dose calculation algorithm. While the WET between experiment and dose calculation agreed within 0.5 mm, except for floral foam, the full width half maximum was underestimated in the TPS by up to 2.3 mm. Normalisation to the same mass thickness of the lung substitutes allowed to classify LTEPs and balsawood as homogeneous and cork, floral foam and konjac sponge as heterogeneous materials. The material specific BP degradation was up to 3.4 times higher for the heterogeneous samples. The modulation power as a measure for the heterogeneity was compared to the spectrum of Hounsfield units (HU) of the materials. A clear correlation was not found, but with further improvements the HU spectrum may serve as an indicator for the material heterogeneity. Further, MC simulations of binary voxel models using GATE/Geant4 were performed to investigate the influence of grain size and mass density. For mass densities similar to lung tissue the BP degradation had a maximum at 3 and 7 mm grain size.